ELECTRONIC VOTING IN ADOPTING RESOLUTIONS OF LIMITED COMPANIES: THE EXAMPLE OF ESTONIAN LAW - Maris Vutt (International Comparative Jurisprudence, 2022)
In the wake of the COVID-19 crisis that began in 2020, countries all over the world had to develop new solutions in legislation to replace various traditionally physical operations with digital solutions. Estonia, with rules in the field of company law and in holding shareholders’ meetings, was no exception. In May 2020, new regulation was introduced into Estonian law, allowing shareholders to participate in meetings using digital means. Although electronic voting itself was already allowed under Estonian law before 2020, the new situation raised a number of legal issues. This article addresses these issues and possible solutions with regard to the legal perspective of electronic voting. As the law does not contain precise requirements for holding an electronic vote, there are many aspects that must be considered in order to comply with the general principles of company law, e.g., how to identify the person giving their vote, and how to ensure the security and reliability of electronic voting. Based on the analysis in this article, the procedure must ensure the identification of shareholders as well as the reliability of casting votes, but must also be proportionate for achieving these aims.